Economics of digital decoupling: a pluralistic analysis - Steffen Lange (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
Digitalization supposedly fosters sustainability and brings about strong economic growth. These promises foster hopes that green growth – that is, to reconcile economic growth with environmental sustainability – is possible. However, digitalization has so far neither led to strong economic growth nor to substantial improvements for environmental sustainability. This article investigates why digitalization has not so far lived up to its promises based on a pluralistic method combining insights from neoclassical and ecological economics, and from post-Keynesian and neo-Marxian perspectives. It finds that the limited effect of digitalization on economic growth is due to its negative effect on aggregate demand, primarily via increasing inequality. The inability of digitalization to substantially improve environmental sustainability can be explained by a combination of distorted relative prices of inputs, missing government investment, and the high environmental footprint of the information and communication technologies sector. It is unclear whether policies to improve the environmental effect of digitalization foster or dampen economic growth. Therefore, gearing digitalization towards supporting environmental sustainability is compatible with an a-growth, rather than a green growth, strategy.
Keywords: 330; digitalization; ecological transformation; economic paradigmsB15; O40; Q55